Walking a tightrope : aboriginal people and their representations - McNab, David, 1947-; Lischke, Ute, 1948- (Waterloo, Ont. : Wilfrid Laurier University Press, 2005)
Annotation "The most we can hope for is that we are paraphrased correctly." In this statement, Lenore Keeshig-Tobias underscores one of the main issues in the representation of Aboriginal peoples by non-Aboriginals. Non-Aboriginal people often fail to understand the sheer diversity, multiplicity, and shifting identities of Aboriginal people. As a result, Aboriginal people are often taken out of their own contexts. Walking a Tightrope plays an important role in the dynamic historical process of ongoing change in the representation of Aboriginal peoples. It locates and examines the multiplicity and distinctiveness of Aboriginal voices and their representations, both as they portray themselves and as others have characterized them. In addition to exploring perspectives and approaches to the representation of Aboriginal peoples, it also looks at Native notions of time (history), land, cultures, identities, and literacies
Seeing red: the stoic whiteman and non-native humour / Drew Hayden Taylor -- Permission and possession: the identity tightrope / Philip Bellfy -- Telling our story / David Newhouse -- A story untold: a community-based oral narrative of Mohawk women's voices from Point Anne, Ontario / Dawn T. Maracle -- Aboriginal representations of history and the Royal Commission on Aboriginal Peoples / Mark Dockstator -- The many faces of Canada's history as it relates to aboriginal people / Olive Patricia Dickason -- The whirlwind of history: parallel nineteenth-century perspectives on "Are they savage?" / Karl Hele -- Reflections on the social relations of indigenous oral histories / Winona Wheeler -- Scientists and evolving perceptions of indigenous knowledge in northern Canada / Stephen Bocking -- Mi'gmaq lives: aboriginal identity in Newfoundland / Dennis Bartels and Alice Bartels -- "Show me the money": representation of aboriginal people in East-German Indian films / Ute Lischke and David T. McNab -- Kwakwaka-wakw on film / Kathryn Bunn-Marcuse -- A way of seeing the world: connecting text, context, and people / Bernie Harder -- Representation of aboriginal peoples in Rudy Wiebe's fiction: The temptations of Big Bear and A discovery of strangers / Janne Korkka.
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Indigenous peoples -- Canada -- Historiography; Indigenous peoples in literature; Indigenous peoples in motion pictures; Indigenous peoples -- Canada -- Ethnic identity; Native peoples -- Canada -- Historiography; Native peoples in literature; Native peoples in motion pictures; Native peoples -- Canada -- Ethnic identity; Peuples autochtones -- Canada -- Historiographie; Autochtones dans la littérature.; Autochtones au cinéma.; Peuples autochtones -- Canada -- Identité ethnique; Autochtones -- Identité ethnique -- Canada; SOCIAL SCIENCE -- Ethnic Studies -- Native American Studies; Indigenous peoples -- Ethnic identity; Indigenous peoples -- Historiography; Indigenous peoples in literature; Indigenous peoples in motion pictures; Canada; Electronic books; Libros electronicos